Spatial Analysis of Gender-Based Violence in Morarano, Toamasina District, Madagascar - Raharijaona Sarindra; Randriamanantena Rakotoarisoa Jaqueline; Rabarison Arsène Andriatiana; Koto-te-Nyiwa Ngbolua (Rowter Journal, 2025)
This study presents a spatial analysis of gender-based violence in the Morarano district, located in Toamasina, Madagascar. Based on a rigorous methodology, the research conducted a field survey among 250 participants, selected by stratified random sampling to ensure representativeness in terms of age, gender, and socioeconomic status. The results indicate that the majority of victims are women. The neighborhoods of Tanambao Verrerie and Analakininina stand out for a significant prevalence of violence ; moreover, the analysis emphasizes the influence of socioeconomic factors that exacerbate family tensions and public space assaults. Intimate partners are identified as the primary aggressors, highlighting dynamics of domestic and interpersonal violence. These findings provide a solid basis for recommendations aimed at improving public policies and preventive actions.